The Effects of Globalized Media on Northern Cultures: A Case Study of Dagomba, Frafra and Wala Ethnic Groups in Tamale Metropolis - Andy Anim; Stephen Oppong; Sarah Geraldo; Mohammed Suruju Gariba; Richard Obeng; Prince Ampiah Ocran; Shormei Naa Odonkor (Journal of Social and Development Sciences, 2022)
The existence of globalized media has influenced most people's ways of living, causing significant changes in Ghana's northern culture. Accepting different civilizations, such as Christian and Islamic civilizations, results in a hybridization of culture, which is shown in their way of life and attitudes regarding issues. This study uses the ethnic groupings of the Dagomba, Frafra, and Wala in Tamale to investigate the effects of globalized media. The study used both quantitative and qualitative research methods to collect relevant data. Using SPSS version 22, it also used descriptive statistics for descriptive analysis and cross-tabulations, as well as the Kendall Coefficient of Concordance to examine the amount of agreement for some specific variables. Out of the ninety people polled, 54 had a television, which they usually used to watch Telenovelas (42.2 %). The outcomes of this study imply that there is a favorable impact on Ghana's northern culture, as seen by their attitude toward social issues (65.6 %) and clothing style (23.3 %). This indicates that while there may be favorable cultural changes, there may also be bad changes. Globalized media, which has the highest rank of 1.73 in the Kendall Coefficient of Concordance, is at the center of it all, playing a vital role in interweaving cultures across time and place. The study suggests that, because the media has a favorable impact on people's attitudes toward social concerns in the north, media houses should promote more social programs